Diplomasi Digital Midwives4all Sebagai Kebijakan Luar Negeri Feminis Swedia di Uganda - Br. Ginting Manik, Junita Yolanda; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The existence of digitalization has influenced all aspects of life, including international relations, the internet revolution requires a country to race against the times by working actively outside the field of traditional diplomacy. The increasing use of online platforms as well as the wider, fast and efficient reach generated by the transformation of the internet has produced new concepts in the field of diplomacy, namely digital diplomacy. In connection with the feminist foreign policy ideas adopted by Sweden, the Midwives4all Campaign launched in 2015 is one of the initiatives taken by Sweden to mobilize support for gender equality and fulfillment of women's human rights in Uganda. This digital campaign enables the Swedish government to project Swedish values and reach various communities in Uganda through various media both online and offline as well as through champions embraced by the Swedish government to build awareness of the important role of midwives in increasing fulfillment of sexual and reproductive health and rights (SRHR) which is one of the six external objectives of Swedish feminist foreign policy. This study intends to explain how the Midwives4all Campaign influences efforts to fulfill women's rights in Uganda. This study will be using qualitative research methods with process-tracing data analysis methods and uses the concept of feminist foreign policy and liberal feminism as the basis for analysis in this paper.